Physical performance tests in male and female sitting volleyball players: Pilot study of Brazilian national team - Ahmadi, S.; Uchida, M. C.; Gutierrez, G. L. (Asian Journal of Sports Medicine, 2019)
Background:Sitting volleyball is a Paralympic team sport in which players use their upper limbs and hands to move and slide across the playing court.